Dysbiosis of Oral and Gut Microbiomes in SARS-CoV-2 Infected Patients in Bangladesh: Elucidating the Role of Opportunistic Gut Microbes - Rafiqul Islam, S. M.; Foysal, Md. Javed; Hoque, M. Nazmul; Mehedi, H. M. Hamidullah; Rob, Md. Abdur; Salauddin, Asma; Tanzina, Afsana Yeasmin; Biswas, Sabuj; Noyon, Sajjad Hossain; Siddiki, A. M. A. M. Zonaed; Tay, Alfred; Mannan, Adnan (Frontiers in Medicine, 2022)
Coronavirus disease-2019 (COVID-19) is an infectious disease caused by SARS-CoV-2 virus. The microbes inhabiting the oral cavity and gut might play crucial roles in maintaining a favorable gut environment, and their relationship with SARS-CoV-2 infection susceptibility and severity is yet to be fully explored. This study investigated the diversity and species richness of gut and oral microbiota of COVID-19 patients, and their possible implications towards the severity of the patient’s illness and clinical outcomes. Seventy-four (n = 74) clinical samples (gut and oral) were collected from 22 hospitalized COVID-19 patients with various clinical conditions, and 15 apparently healthy people (served as controls). This amplicon-based metagenomic sequencing study yielded 1,866,306 paired-end reads that were mapped to 21 phyla and 231 classified genera of bacteria. Alpha and beta diversity analyses revealed a distinct dysbiosis of the gut and oral microbial communities in COVID-19 patients, compared to healthy controls. We report that SARS-CoV-2 infection significantly reduced richness and evenness in the gut and oral microbiomes despite showing higher unique operational taxonomic units (OTUs) in the gut. The gut samples of the COVID-19 patients had an inclusion of 46 opportunistic bacterial genera. Escherichia, Shigella and Bacteroides were detected as the signature genera in the gut of COVID-19 patients with diarrhea whereas relatively higher abundance of Streptococcus was found in COVID-19 patients having breathing difficulties and sore throat. The COVID-19 patients had significantly lower abundance of Prevotella in the oral cavity, compared to healthy controls and COVID-19 patients without diabetes, respectively. The altered metabolic pathways including a reduction in biosynthesis capabilities of the gut and oral microbial consortia after SARS-CoV-2 infection were also observed. The present study may, therefore, shed light on interactions of SARS-CoV-2 with resilient oral and gut microbes which might contribute towards developing microbiome-based diagnostics and therapeutics for this deadly pandemic disease.